Prevention of blindness and priorities for the future - West Sheila; Sommer Alfred (The World Health Organization, 2001)
The impact of visual loss has profound implications for the person affected and society as a whole. The majority of blind people live in developing countries, and generally, their blindness could have been avoided or cured. Given the current predictions that the number of blind people worldwide will roughly double by the year 2020, it is clear that there is no room for complacency. As the world?s population increases and as a greater proportion survives into late adulthood, so the number of people with visual loss will inexorably rise. Given the success of programmes in combating the most common causes of blindness (infectious diseases and malnutrition) which generally affect the young, and the projected demographic shift, age-related eye disease will become increasingly prevalent. Effective preventive measures for these diseases can only be established as more is known about their etiology. As the longevity of the world?s population increases, the visual requirements at the workplace are also changing. People with low vision may be at a disadvantage in many common activities, and may face unemployment - particularly in technological societies. The definition of blindness needs to be rethought, to ensure that people with ??economic?? blindness are not forgotten. Efforts should be made to recognize and treat those affected at an early stage, for the benefit of the individual and society.